Mutiara pearls of the Malay Archipelago - Harun Rahman (Kuala Lumpur : Novista Sdn Bhd [production company] ; Melaka : Usahasama Edaran Timor [distributor], 1998)
Explore the isle of Mabul, a precious gem among the ligitan group of island in Borneo - a visit to a tiny oceanic island (Sipadan) that rests on a pinnacle of volcanic rock, rising 2000feet from the bottom of the sea - venture out to Pandanan, a tiny island of sand - journey to the remote island in the Spratleys (Layang-layang)
episode 1. The sand dwellers of Mabul - episode 2. Sipadan : centre of the fish universe - episode 3. Pandanan : realm of the camouflage artist - episode 4. Layang-layang : coral gardens of the South China Sea
Copy available in DVD format
Script, Chin Kek Mie, Lara Ariffin ; editor, M Baskaran, Harun Rahman, Lara Ariffin
Narrator: Noraini Jane Ariffin
Keywords: Underwater exploration; Underwater archaelogy; Sabah -- Description and travel